Spectral Dependence on Sampling Frequency in Static Modulated Fourier Transform Infrared Spectrometer - Yong Cho, Ju; Kyu Park, Hyun; Seok Ji, Min; Kweon Jang, Won (Asian Journal of Chemistry, 2015)
The spectral dependence on the sampling frequency in the Fourier transform infrared spectrometer was discussed for the exact spectral information. To get the optimized sampling frequency without superfluous or insufficient data, two spectra of the solid sample in two different data spacing were compared in the three spectral ranges. The difference of spectral data of two different data spacing showed a decrease in the higher wavenumber region.